2012
DOI: 10.1002/jbm.b.32708
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the resin–dentin bonds after simulated and inhibited cariogenic challenge in an in situ model

Abstract: The aim of this study was to evaluate the resin–dentin bonds of two simplified etch‐and‐rinse adhesive after simulated cariogenic and inhibited cariogenic challenge in situ. Dental cavities (4 mm wide, 4 mm long, and 1.5 mm deep) were prepared in 60 bovine teeth with enamel margins. Restorations were bonded with either adhesive Adper Single Bond 2 (3MESPE) or Optibond Solo Plus (Kerr). Forty restorations were included in an intra‐oral palatal appliance that was used for 10 adult volunteers while the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
1
9
0
5
Order By: Relevance
“…Moreover, the incorporation of PAMAM and DMADDM regulated the bacteria ratio of the three-species biofilms and help to develop a biofilm with lower cariogenic S. mutans proportion and reduced possibility of dental caries. Previous studies showed that it was favorable for adhesive to inhibit or kill residual bacteria in the prepared tooth cavity, as well as invading bacteria at the tooth-restoration interface through marginal leakage [18,19]. In the present study, the adhesive containing 5% DMADDM and 1% PAMAM + 5% DMADDM had strong antibacterial effect, which was consistent with previous studies [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the incorporation of PAMAM and DMADDM regulated the bacteria ratio of the three-species biofilms and help to develop a biofilm with lower cariogenic S. mutans proportion and reduced possibility of dental caries. Previous studies showed that it was favorable for adhesive to inhibit or kill residual bacteria in the prepared tooth cavity, as well as invading bacteria at the tooth-restoration interface through marginal leakage [18,19]. In the present study, the adhesive containing 5% DMADDM and 1% PAMAM + 5% DMADDM had strong antibacterial effect, which was consistent with previous studies [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…the micro-tensile test and the shear test [16, 23]. Because the specimens are small in the micro-tensile test, extensive machining is required which can lead to large amount of premature failure and significant variation in bond strength measurement.…”
Section: Discussionmentioning
confidence: 99%
“…One of these processes involves the pH fluctuations caused by cariogenic challenges, which can reduce bond strength. 23 In addition, in situ models are appropriate for evaluating bond degradation because host-derived MMPs can originate from saliva and from dentin. 24 Recently, Reinke and others 23 reported that the in situ model seems to be a suitable short-term methodology to investigate the degradation of resin-dentin bonds under a more realistic condition.…”
Section: Introductionmentioning
confidence: 99%